The answer is the first one: (z+1)(y+6).
Explanation:
yz + 6 + y + 6z
= yz + y + 6 + 6z
= y(z+1) + 6(1+z)
= (z+1)(y+6)
For (z+1), you can also write (1+z), it doesn’t matter.
Hope it helps!
Answer:
Step-by-step explanation:
she started off with 44 boxes
Answer:
5 = 6q - 30 - 19
5 = 6q - 49
54 = 6q
9 = q
Step-by-step explanation:
Answer:
x=4.5
y=5.75
Step-by-step explanation:
since you dont have much time to wait, i wont put an explanation here
The most important thing that you have to know is that all angles in a triangle equals 180°